Media Literacy Skills and Social Media: A Portray of Teenagers in Urban Area - Tri Atmi, Ragil; F. Satibi, Iswanda; R. Cahyani, Indah (International Journal of Engineering and Technology, 2018)
What we know about association between social media and media literacy is largely based upon case studies that investigate how teenagersâ€™ behavior in digital environment. Although studies focusing on the level of media literacy skills towards social media have been conducted in recent years, much uncertainty still exists about the relationship between the media literacy skills and the use of social media among teenagers. This study aims to contribute to this growing area of research by exploring the level of media literacy skills and motivations among the teenagers towards social media in urban area. A quantitative descriptive survey research design was used to identify, analyze, and describe the media literacy skills of teenagers towards social media. The purposive sampling method was taken to appropriately select an evenly balanced group of participants. In total, 34 students participated, of which 83% living in the rural-urban fringe area, the intersection area between urban and farming field. It is evidently clear from the findings that the average level of media literacy skills among teenagers in urban area is at medium level. There is a high level of information dimension among teenagers, whereas other dimensions are fractionally less popular. On average, the level of dimensional motivations is medium. Teenagers seem to use social media to support their study and socially engage with friends. The result of this study confirm previous studies that focused on the level of media literacy among teenagers towards social media. Analysis of data shows that teenagers acknowledged the benefits of social media. However, no statistically significant difference between the mean sores of four sets of media literacy skills was evident. Media literacy is maturing, as evidenced by the significant understanding of social media in the digital environment.Â Â